2020
DOI: 10.1101/2020.09.16.300079
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evidences for a nutritional role of iodine in plants

Abstract: Little is known about the role of iodine in plant physiology. We evaluated the impact of low concentrations of iodine on the phenotype, transcriptome and proteome of Arabidopsis thaliana. Our experiments showed that removal of iodine from the nutrition solution compromises plant growth, and restoring it in micromolar concentrations is beneficial for biomass accumulation and leads to early flowering. In addition, iodine treatments specifically regulate the expression of several genes, mostly involved in the pla… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 73 publications
(81 reference statements)
1
9
0
Order By: Relevance
“…Iodine can be incorporated into various organic compounds such as proteins, lipids, polysaccharides and polyphenols ( Millard, 1988 ; Hou, 2009 ), and occurs naturally in the form of triiodothyronines or other iodo-tyrosins in lettuce and tomato plants even if they are not receiving exogenous I ( Halka et al, 2019 ; Sularz et al, 2020 ). Recently, in a study on proteomics in Arabidopsis thaliana (L.), I has been found to be organified in many important regulatory proteins of the plant, pointing to a nutritional role of I for plants at concentrations which are generally much lower than the I levels applied for purpose of biofortification ( Kiferle et al, 2020 ). So far, little is known about which of these organic I species play a major role in I-fertilized plants.…”
Section: Introductionmentioning
confidence: 99%
“…Iodine can be incorporated into various organic compounds such as proteins, lipids, polysaccharides and polyphenols ( Millard, 1988 ; Hou, 2009 ), and occurs naturally in the form of triiodothyronines or other iodo-tyrosins in lettuce and tomato plants even if they are not receiving exogenous I ( Halka et al, 2019 ; Sularz et al, 2020 ). Recently, in a study on proteomics in Arabidopsis thaliana (L.), I has been found to be organified in many important regulatory proteins of the plant, pointing to a nutritional role of I for plants at concentrations which are generally much lower than the I levels applied for purpose of biofortification ( Kiferle et al, 2020 ). So far, little is known about which of these organic I species play a major role in I-fertilized plants.…”
Section: Introductionmentioning
confidence: 99%
“…The hypothesis that the iodide is responsible for the toxicity at low MAPbI3 concentrations is further confirmed by the absence of toxicity of MABr and PbBr2 in the same concentration ranges (Figure 2C). While iodide is considered a (micro-) nutrient, 12 the toxicity effects of iodide at higher concentrations are poorly understood. Our conclusion that that the low toxicity threshold of MAPbI3 is caused by the presence of iodide, rather than lead, stresses the importance of further investigating the environmental effects of using iodide salts in solar panels.…”
Section: Resultsmentioning
confidence: 99%
“…Although I biofortification in plants was deeply investigated (Cheng 1981, Blasco et al 2011, Kiferle et al 2021, Izydorczyk et al 2021, there is a lack of information about the ameliorative effects on photosynthesis related to I if compared to other elements used in plant biofortification such as Se (Table 4). This was probably due to the high I toxicity for plants and to the difficulty to find the concentration at which this element can be useful for plant growth.…”
Section: Iodinementioning
confidence: 99%
“…To date, a detailed report of Kiferle et al (2021) using Arabidopsis plants, revealed the existence of several iodinated proteins involved in photosynthesis, such as constituents of PSII (PsbA, PsbB, PsbC, and PsbD), OEC (PsbO, PsbP, PsbQ, and PsbR), LHCII (CAB3, LHCB2.1, LHCB1B1, LHCB3, LHCB5), PSI (PsaB, PsaE, PsaF, and PsaH), Cyt b6/f (PetA and PetC), plastocyanin electron carrier (PETE2), and ferredoxin-NADP(+)oxidoreductase (FNR1). Moreover, other iodinated proteins were involved in the development/maintenance of both photosystems (Psb27, Psb29, Psb31, and Psb33), in PSII photoprotection (MPH1) or in the degradation of the photodamaged D1 reaction centre.…”
Section: Iodinementioning
confidence: 99%
See 1 more Smart Citation